PENERAPAN PEWARNAAN GRAF PADA PENEMPATAN KAMAR MAHASISWA (STUDI KASUS: MA’HAD AL-JAMI’AH UNIVERSITAS ISLAM NEGERI SALATIGA) - Kurnia Abda Rahmani; Yuni Setyaningsih; Sinta Nur Anjarwati; Muhammad Sirril Wafa; Muhamad Gani Rahman (STKIP Paracendekia NW Sumbawa, 2024)
Effective room allocation in student dormitories is crucial for creating a comfortable and supportive learning environment. This study aims to apply graph coloring techniques to the room allocation of students at Ma’had Al-Jami’ah of the State Islamic University of Salatiga. Student data and their respective study programs are modeled as vertices in a graph to prevent students from the same study program from being placed in the same room. The Welch Powell Algorithm is used for graph coloring, ensuring that each room accommodates students from different study programs. The results indicate that graph coloring is effective in reducing potential conflicts and promoting cross-disciplinary interaction, resulting in a more inclusive and diverse dormitory environment.